Adaptive Health Management Information Systems: Concepts, Cases, & Practical Applications - Tan Hoan Tjay (Jones & Bartlett Learning, 2009)
This book covers all the fundamental concepts of Health Management Information Systems (HMIS), provides relevant and current HMIS cases throughout, and touches on emerging technologies. Topics include: information systems from a managerial perspective; roles of cio/cto for healthcare services organizations; HMIS hardware/software concepts; HMIS database concepts; HMIS standards, privacy, and security concepts; HMIS communications and networking concepts; HMIS strategic planning; HMIS investigation & analysis; HMIS design, implementation, and evaluation; e-healthcare information systems; healthcare information systems; use of HMIS emerging technologies and its impact on human health.